2021
DOI: 10.7717/peerj.10791
|View full text |Cite
|
Sign up to set email alerts
|

An integrative approach to infer systematic relationships and define species groups in the shrub frog genusRaorchestes, with description of five new species from the Western Ghats, India

Abstract: The genus Raorchestes is a large radiation of Old World tree frogs for which the Western Ghats in Peninsular India is the major center for origin and diversification. Extensive studies on this group during the past two decades have resolved long-standing taxonomic confusions and uncovered several new species, resulting in a four-fold increase in the number of known Raorchestes frogs from this region. Our ongoing research has revealed another five new species in the genus, formally described as Raorchestes drut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Communication signals may be predicted to exhibit diversity in support of these varied functions. In hyper-diverse regions such as the Western Ghats, understanding and quantifying this behavioral diversity may provide both scientific insight and important inputs for conservation (Garg et al 2021). Recent literature suggests that behavioral diversity must be considered when assessing biodiversity for conservation (Caro and Sherman 2012; Cooke et al 2014; Cordero-Rivera 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Communication signals may be predicted to exhibit diversity in support of these varied functions. In hyper-diverse regions such as the Western Ghats, understanding and quantifying this behavioral diversity may provide both scientific insight and important inputs for conservation (Garg et al 2021). Recent literature suggests that behavioral diversity must be considered when assessing biodiversity for conservation (Caro and Sherman 2012; Cooke et al 2014; Cordero-Rivera 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nyctibatrachus and Pseudophilautus have both evolved in the Western Ghats-Sri Lanka biodiversity hotspot (Van Bocxlaer et al 2012; Vijayakumar et al 2016; Meegaskumbura et al 2019; Torsekar 2019). Although studies of anuran vocalizations from this region have characterized taxonomic diversity (Garg et al 2021), relatively little remains known about vocal behavior. Members of both lineages use vocalizations to communicate and are prolonged, territorial breeders (Gramapurohit et al 2011; Bee, Suyesh, et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They credit Garg et al (2021) for highlighting the shallow divergence between the species. However, the findings were first presented by Mirza et al (2019) and confirmed by Garg et al (2021). This suggests a poor literature review by Narayanan et al (2021).…”
mentioning
confidence: 99%
“…Shallow divergence: Narayanan et al (2021) draw attention to the case of shallow genetic divergence between R. bombayensis (Annandale, 1919) and R. sanctisilvaticus (Das & Chanda, 1997), which are broadly distributed across the Western Ghats and the Eastern Ghats respectively (Biju & Bossuyt 2009;Garg et al 2021;Mirza et al 2019). They credit Garg et al (2021) for highlighting the shallow divergence between the species. However, the findings were first presented by Mirza et al (2019) and confirmed by Garg et al (2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation